Analisis Kemampuan Berpikir Kritis Siswa dalam Menyelesaikan Soal Tipe Open Ended Ditinjau dari Motivasi Belajar pada Materi SPLTV - Hellen Dita Natassya; Rizky Esti Utami; Widya Kusumaningsih (Perkumpulan Kualitama Edukatika Indonesia, 2023)
This study aims to determine students' critical thinking skills in solving open ended type questions in terms of learning motivation on System of Linear Equations with Three Variables material. This research is a qualitative descriptive study. This research was conducted in class XI IPA 1 and XI IPA 2 SMA Institut Indonesia Semarang which were selected based on the results of the questionnaire test and the results of the test instrument trials. The research subjects were selected based on a learning motivation questionnaire from 24 students of class XI IPA 1, 3 students were selected consisting of one subject with high learning motivation, one subject with moderate learning motivation, and one subject with low learning motivation. Data collection techniques using learning motivation questionnaire instruments, written tests, documentation. In the research technique analysis is carried out, namely reducing data, presenting data, and drawing conclusions. Data validity checking technique uses technical triangulation. The results showed that 1) students with high learning motivation were able to fulfill all indicators of critical thinking, namely interpretation, analysis, evaluation, inference, explanation, and self-regulation, 2) students with moderate learning motivation were only able to fulfill 4 indicators of critical thinking, namely analysis, evaluation, inference, and self-regulation, 3) students with low learning motivation are only able to meet the indicators of critical thinking analysis and evaluation.